EVALUASI PROGRAM IN HOUSE TRAINING MELALUI PBD (PERENCANAAN BERBASIS DATA) DALAM UPAYA TRANSFORMASI KOMPETENSI PEDAGOGIK GURU SD (STUDI KASUS DI SDN TANJUNGBIRU DAN SD AL MU’MIN, KABUPATEN BANDUNG) - Fitrianingsih; Yoseptry, Ricky; Ningsih, Muhammad Gaffar (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This research is motivated by the ongoing gap between the demands of teacher pedagogical competency and learning practices in the field. Although educational policies have encouraged data-based learning, in reality the utilization of data such as educational report cards has not been maximized and tends to be administrative. The In House Training (IHT) program through data-based planning (PBD) is presented as a strategic solution, but its effectiveness still needs to be evaluated comprehensively. This study aims to evaluate the IHT program through PBD in transforming the pedagogical competency of elementary school teachers through an analysis of the context, input, process, and product of the program at SDN Tanjungbiru and SD Al Mu'min. Theoretically, this research is based on the grand theory of program evaluation of the CIPP model from Stufflebeam, the middle theory of teacher pedagogical competency, and applied theory in the form of the implementation of IHT through PBD as a strategy to improve teacher professionalism based on real needs in schools. This research uses a qualitative approach with a program evaluation method. Data collection techniques are carried out through observation, interviews, and documentation studies, then analyzed interactively through data reduction, data presentation, and drawing conclusions. The results of the study indicate that: (1) in the context aspect, the program has been in accordance with the needs to improve teacher competency even though the use of data has not been maximized; (2) input, planning, and resources are adequate, but understanding of PBD is still limited; (3) process, implementation is proceeding according to plan with active teacher participation; and (4) product, the program has a positive impact on changes in planning and learning practices, although this is not yet evenly distributed. Overall, the In-House Training (IHT) Program through PBD has proven to be able to transform teachers' pedagogical competencies toward more reflective, contextual, and student-oriented learning practices, although it still requires strengthening in data literacy and mentoring for maximum and sustainable impact.